2009
DOI: 10.1016/j.jbiomech.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flow field around a human hand and propulsive force in swimming

Abstract: Much effort has been undertaken for the estimation of propulsive force of swimmers in the front crawl. Estimation is typically based on steady flow theory: so-called the quasi-steady analysis. Flow fields around a swimmer, however, are extremely unsteady because the change direction of hand produces unsteady vortex motions. To evaluate the force correctly, it is necessary to know the unsteady properties determined from the vortex dynamics because that unsteadiness is known to make the force greater. Unsteady f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 13 publications
1
45
0
3
Order By: Relevance
“…Such results were complemented with 2-D [60] and 3-D [61] PIV studies to analyse the stroke of a robotic arm in water. In both approaches, the motion resulted in the production of vortices [4], similar to those previously observed [59] when the hand adapted its orientation. An important advantage of PIV is that it does not disturb the swimmer's actions [55] in experiments.…”
Section: Fluid Perturbations From Swimmer's Movementsupporting
confidence: 65%
See 3 more Smart Citations
“…Such results were complemented with 2-D [60] and 3-D [61] PIV studies to analyse the stroke of a robotic arm in water. In both approaches, the motion resulted in the production of vortices [4], similar to those previously observed [59] when the hand adapted its orientation. An important advantage of PIV is that it does not disturb the swimmer's actions [55] in experiments.…”
Section: Fluid Perturbations From Swimmer's Movementsupporting
confidence: 65%
“…A similar method is particle image velocimetry (PIV), a technique that uses a laser to track illuminated particles introduced into fluids (see [58]). This experimental approach has been used in competitive swimming to identify fluid motions associated with an upper limb stroke [59][60][61], a sculling sequence [62] and a dolphin kick [63]. A pioneer PIV work [59] focused on fluid perturbations occasioned by a front crawler's hand.…”
Section: Fluid Perturbations From Swimmer's Movementmentioning
confidence: 99%
See 2 more Smart Citations
“…Using PIV Matsuuchi et al (2004) first demonstrated the flow field occurring around a moving hand while swimming, which may be the main source of propulsion for the crawl stroke. Momentum generation was estimated from this flow field obtained through PIV (Matsuuchi et al (2009). According to Newton's second law of motion, the increment of momentum leads directly to the force generation.…”
mentioning
confidence: 99%